2011
DOI: 10.1016/j.ajhg.2011.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Primary Ciliary Dyskinesia Caused by Homozygous Mutation in DNAL1, Encoding Dynein Light Chain 1

Abstract: In primary ciliary dyskinesia (PCD), genetic defects affecting motility of cilia and flagella cause chronic destructive airway disease, randomization of left-right body asymmetry, and, frequently, male infertility. The most frequent defects involve outer and inner dynein arms (ODAs and IDAs) that are large multiprotein complexes responsible for cilia-beat generation and regulation, respectively. Although it has long been suspected that mutations in DNAL1 encoding the ODA light chain1 might cause PCD such mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(67 citation statements)
references
References 40 publications
2
64
0
Order By: Relevance
“…Pro residues can exist in either cis or trans conformations (Fig. 7), and molecular modeling revealed that a cis-Pro residue is readily accommodated within the wild-type structure 15 N HSQC spectra for wild-type and the M182A, D185G, D185P, R189E, and R196A mutant forms of LC1 are shown in the lower panels. Each peak represents an amide resonance derived from the peptide backbone, Asn/Gln side chains, or the Trp indole ring.…”
Section: Perturbations Caused By Dominant Negative Mutations In Lc1 Cmentioning
confidence: 99%
See 3 more Smart Citations
“…Pro residues can exist in either cis or trans conformations (Fig. 7), and molecular modeling revealed that a cis-Pro residue is readily accommodated within the wild-type structure 15 N HSQC spectra for wild-type and the M182A, D185G, D185P, R189E, and R196A mutant forms of LC1 are shown in the lower panels. Each peak represents an amide resonance derived from the peptide backbone, Asn/Gln side chains, or the Trp indole ring.…”
Section: Perturbations Caused By Dominant Negative Mutations In Lc1 Cmentioning
confidence: 99%
“…Even so, the number of residues exhibiting significant ⌬␦ values suggests that the observed phenotypes cannot necessarily be ascribed to the mutation of a particular residue but rather may reflect a more global perturbation or reorientation of this domain. To address this directly, we reassigned the backbone for 13 C, 15 Nlabeled D185G LC1 from 1 H-15 N HSQC, HNCA, HNCO, and HBHA(CO)NH spectra and performed a TALOSϩ backbone chemical shift analysis. This revealed that the overall helical structure of the C-terminal domain was not greatly perturbed but that the and angles for residues surrounding the mutation site were significantly changed (Fig.…”
Section: Perturbations Caused By Dominant Negative Mutations In Lc1 Cmentioning
confidence: 99%
See 2 more Smart Citations
“…To date mutations have been identified in 6 genes encoding for proteins that are part of the ODA (DNAH5, DNAI1, DNAI2, DNAL1, NME8 (TXNDC3) and DNAH11) [12,[71][72][73][74][75]. Mutations in DNAH5 and DNAI1 are thought to account for the largest proportion of PCD patients: 30% and 9% respectively [19,[76][77][78][79].…”
Section: Genetics: Pcd Is Generally An Autosomal Recessive Disease Tmentioning
confidence: 99%